Transcriptional and bioinformatic analysis of GABAA receptors expressed in oligodendrocyte progenitor cells from the human brain - Gutierrez, Berenice A.; González-Coronel, José Manuel; Arellano, Rogelio O.; Limon, Agenor (Frontiers in Molecular Neuroscience, 2023)
Introduction Oligodendrocyte progenitor cells (OPCs) are vital for neuronal myelination and remyelination in the central nervous system. While the molecular mechanisms involved in OPCs’ differentiation and maturation are not completely understood, GABA is known to positively influence these processes through the activation of GABAA receptors (GABAARs). The molecular identity of GABAARs expressed in human OPCs remains unknown, which restricts their specific pharmacological modulation to directly assess their role in oligodendrocytes’ maturation and remyelination. Methods In this study, we conducted a transcriptomic analysis to investigate the molecular stoichiometry of GABAARs in OPCs from the human brain. Using eight available transcriptomic datasets from the human brain cortex of control individuals, we analyzed the mRNA expression of all 19 known GABAARs subunit genes in OPCs, with variations observed across different ages. Results Our analysis indicated that the most expressed subunits in OPCs are α1–3, β1–3, γ1–3, and ε. Moreover, we determined that the combination of any α with β2 and γ2 is likely to form heteropentameric GABAARs in OPCs. Importantly, we also found a strong correlation between GABAAR subunits and transcripts for postsynaptic scaffold proteins, suggesting the potential postsynaptic clustering of GABAARs in OPCs. Discussion This study presents the first transcriptional-level identification of GABAAR subunits expressed in human OPCs, providing potential receptor combinations. Understanding the molecular composition of GABAARs in OPCs not only enhances our knowledge of the underlying mechanisms in oligodendrocyte maturation but also opens avenues for targeted pharmacological interventions aimed at modulating these receptors to promote remyelination in neurological disorders.